The Impact of Resource Spatial Mismatch on the Configuration Analysis of Agricultural Green Total Factor Productivity - Chen, Pengwei; Ding, Xuhui; Chen, Mo; Song, Huiqi; Imran, Muhammad (Agriculture (Basel), 2025)
Green agriculture represents the future of agricultural transformation in developing countries, such as China. Identifying an effective resource combination path is vital for enhancing the green quality of agriculture in these nations. This study draws on the resource spatial mismatch theory from New Economic Geography, using a “multisource heterogeneous” approach that combines qualitative comparative analysis (QCA) with the EBM-GML index measurement model. Using panel data from 2005 to 2021, the study investigated the effects and mechanisms of spatial resource combinations on improving green agricultural quality. The key findings are as follows: (1) While improving spatial resource misallocation helps boost green agricultural quality, the diversity of resource combination patterns has diminished, decreasing from five modes in 2005 to four in 2021. (2) In terms of mechanisms, reducing externalities, such as pollutant emissions, while strengthening material and human capital offers a potential pathway for improvement. (3) Negative externalities, including emissions from fertilizers and petroleum, significantly hinder improvements in green agricultural quality. (4) The absence of sufficient pesticide and fertilizer resources is a critical factor influencing the outcome. These findings provide practical insights for developing countries seeking to enhance regional resource allocation efficiency and improve agricultural green quality. Additionally, they contribute theoretical support to the enrichment of theories on resource allocation and sustainable agricultural development.